Cardio-Oncology: A Myriad of Relationships Between Cardiovascular Disease and Cancer - Wang, Yinghui; Wang, Yonggang; Han, Xiaorong; Sun, Jian; Li, Cheng; Adhikari, Binay Kumar; Zhang, Jin; Miao, Xiao; Chen, Zhaoyang (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular disease (CVD) and cancer are the leading causes of death worldwide. With an increasing number of the elderly population, and early cancer screening and treatment, the number of cancers cases are rising, while the mortality rate is decreasing. However, the number of cancer survivors is increasing yearly. With the prolonged life span of cancer patients, the adverse effects of anti-tumor therapy, especially CVD, have gained enormous attention. The incidence of cardiovascular events such as cardiac injury or cardiovascular toxicity is higher than malignant tumors' recurrence rate. Numerous clinical studies have also shifted their focus from the study of a single disease to the interdisciplinary study of oncology and cardiology. Previous studies have confirmed that anti-tumor therapy can cause CVD. Additionally, the treatment of CVD is also related to the tumors incidence. It is well established that the increased incidence of CVD in cancer patients is probably due to an unmodified unhealthy lifestyle among cancer survivors or cardiotoxicity caused by anti-cancer therapy. Nevertheless, some patients with CVD have a relatively increased cancer risk because CVD and malignant tumors are highly overlapping risk factors, including gender, age, hypertension, diabetes, hyperlipidemia, inflammation, and obesity. With advancements in the diagnosis and treatment, many patients simultaneously suffer from CVD and cancer, and most of them have a poor prognosis. Therefore, clinicians should understand the relationship between CVD and tumors, effectively identify the primary and secondary prevention for these diseases, and follow proper treatment methods.